The Effect Of Bank Soundness Level On Stock Price Sensitivity: A Study On Banking Companies Listed On The Indonesia Stock Exchange For The 2018-2022 Period - Selvia Mely Nova; Marlina Widiyanti; Muizzuddin Muizzuddin; Mohamad Adam (Journal of Social Research, 2024)
The purpose of this study is to obtain empirical evidence of the Earning Per Share, Non Performing Loan, Capital Adequency Ratio, and Good Corporate Governance on the Banking Company srock price listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, the research samples obtained totaled 29 companies with a research period from 2018-2022 so that there were 145 units of analysis. The research design was quantitative descriptive. The analysis technique in this research is multiple regression analysis method. The results showed that Earning Per Share and Non Performing Loan has a significant positive effect, Capital Adequency Ratio, and Good Corporate Governance has no effect on stock price. The implication of this research is that companies must pay attention to Earning Per Share and Non Performing Loan, and those that can affect stock price quality.